The northern North Atlantic Ocean mean circulation in the early 21st century. (August 2016) - Daniault, Nathalie; Mercier, Herlé; Lherminier, Pascale; Sarafanov, Artem; Falina, Anastasia; Zunino, Patricia; Pérez, Fiz F.; Ríos, Aida F.; Ferron, Bruno; Huck, Thierry; Thierry, Virginie; Gladyshev, Sergey
Highlights: Northern North Atlantic ocean circulation is quantified. Circulation schemes for the upper, intermediate and deep layers are derived. New pathways for the North Atlantic Current branches are proposed. The fate of the intermediate water flow across the Mid-Atlantic Ridge is identified. Three veins of Iceland Scotland Overflow Water are found in the Iceland Basin. Abstract: The decadal mean circulation in the northern North Atlantic was assessed for the early 21st century from repeated ship-based measurements along the Greenland-Portugal OVIDE line, from satellite altimetry and from earlier reported transports across 59.5°N and at the Greenland-Scotland sills. The remarkable quantitative agreement between all data sets allowed us to draw circulation pathways with a high level of confidence. The North Atlantic Current (NAC) system is composed of three main branches, referred to as the northern, central and southern branches, which were traced from the Mid-Atlantic Ridge (MAR), to the Irminger Sea, the Greenland-Scotland Ridge and the subtropical gyre. At OVIDE, the northern and central branches of the NAC fill the whole water column and their top-to-bottom integrated transports were estimated at 11.0 ± 3 Sv and 14.2 ± 6.4 Sv (1 Sv = 10 6 m 3 s −1 ), respectively. Those two branches feed the cyclonic circulation in the Iceland Basin and the flow over the Reykjanes Ridge into the Irminger Sea. This cross-ridge flow was estimated at 11.3 ± 4.2 Sv westward, north of 58.5°N. The southern NAC branch is strongly surface-intensified and most of its top-to-bottom integrated transport, estimated at 16.6 ± 2 Sv, is found in the upper layer. It is composed of two parts: the northern part contributes to the flow over the Rockall Plateau and through the Rockall Trough toward the Iceland-Scotland Ridge; the southern part feeds the anticyclonic circulation toward the subtropical gyre. Summing over the three NAC branches, the top-to-bottom transport of the NAC across OVIDE was estimated at 41.8 ± 3.7 Sv. Because of the surface-intensification of the southern NAC branch, the intermediate water is transported to the northeast Atlantic mostly by the northern and central branches of the NAC (11.9 ± 1.8 Sv eastward). This water circulates cyclonically in the Iceland Basin and anticyclonically in the West European Basin, with similar transport intensities. In the deep layer of the Iceland Basin, Iceland-Scotland Overflow Water (ISOW) spreads southwestward along three pathways on the eastern flank of the Reykjanes Ridge. The associated transport was estimated at 3.2 ± 0.4 Sv. The two shallowest pathways turn around the Reykjanes Ridge toward the Irminger Sea where they head northward. A northeastward transport of deep water is observed in the deep extension of the northern and central branches of the NAC, east of the MAR. In the Irminger Sea our transport estimates for the Irminger Current, Irminger Gyre, East Greenland Irminger Current and Deep Western Boundary Current are in line with previous work.